2021
DOI: 10.47688/rdp2021-09
|View full text |Cite
|
Sign up to set email alerts
|

Is the Phillips Curve Still a Curve? Evidence from the Regions

Abstract: The way in which wages respond to very low rates of unemployment remains a key source of uncertainty in Australia, partly due to the lack of historical evidence to draw upon. To help fill this gap, we study data on unemployment rates and wages growth across local labour markets over the past 20 years. The considerable variation in economic conditions across local labour markets allows us to infer the strength of the relationship between unemployment and wages growth (i.e. the wage Phillips curve) at very low u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
3
1
0
Order By: Relevance
“…The authors found that wage rates rise steeply when unemployment is low, and the changes in wages become flat at high unemployment rates. The same conclusion was observed by Bishop and Greenland (2021) in the case of Australia. Similarly, Cristini and Ferri (2021) examined the different types and degrees of nonlinearity in the price Phillips curve in the USA over the period 1961Q1-2019Q4, deploying both pairwise and threshold techniques.…”
Section: Literature Reviewsupporting
confidence: 84%
“…The authors found that wage rates rise steeply when unemployment is low, and the changes in wages become flat at high unemployment rates. The same conclusion was observed by Bishop and Greenland (2021) in the case of Australia. Similarly, Cristini and Ferri (2021) examined the different types and degrees of nonlinearity in the price Phillips curve in the USA over the period 1961Q1-2019Q4, deploying both pairwise and threshold techniques.…”
Section: Literature Reviewsupporting
confidence: 84%
“…This finding validates Phillip's (1958) theoretical argument that inflation increases steeply when unemployment is low, and the change in inflation becomes flat at a high unemployment rate. This outcome is congruent with the findings of Kumar and Orrenius (2015), Nalewaik (2016), Albuquerque and Baumann (2017), Bryne and Zekaite (2017), Bishop andGreenland (2021), andOnatunji et al (2023), who discovered similar findings in their investigations. Additionally, the results show that positive (rising) unemployment has a significant negative effect on inflation, while negative (declining) unemployment has an insignificant negative impact on inflation in Cape Verde, Gambia, and Guinea-Bissau.…”
Section: Resultssupporting
confidence: 92%
“…The results reveal that wage rates increase significantly when unemployment is low, and the rate of change in wages becomes con- Trade-off stant at high unemployment levels. Bishop and Greenland (2021) found similar results when examining the Australian economy. Furthermore, Cristini and Ferri (2021) studied the various forms and levels of nonlinearity in the price Phillips curve in the United States over the period 1961Q1-2019Q4 by employing both pairwise and threshold techniques.…”
Section: Brief Literature Reviewsupporting
confidence: 55%
“…Babecka, et al (2022) confirmed the cyclical dynamics of inflation according to the PC for the Czech economy as well. Bishop and Greenland (2021) find strong evidence that the wage PC is indeed a curve rather than a straight line. Hronova, et al (2021) draw attention to the fact that the indicators of the inflation rate and the unemployment rate are still necessary to evaluate the trend of the difference in their values over time.…”
Section: Geographical Overview Of the Pandemic Topic In The Period 20...mentioning
confidence: 89%